Repeated sprint and dribbling ability among Malaysian university soccer players / Annisaa Basar - Basar, Annisaa (2015)
The purpose of the present study was to determine the relationships between repeated sprints ability (RSA) and repeated dribbling ability (RDA) with aerobic power, leg power and blood lactate. Fifiy two, well-trained soccer players (age: 21.7311.82years, height: 171.31i5.27cm, weight: 63.78i7‘30kg, BMI: 21.69i2.29kg.m") participated in this study were enrolled university students. All were members of top three teams (UiTM, UM, UKM) from the first division of Malaysian Higher Education Institution soccer league, 2013. Participants performed all four tests: 20Multistages Shuttle Run Test, vertical jump, RSA, RDA and blood lactate concentration. The V02,“x was measured by ZOMST, while leg power was measured by vertical jump. The RSA and RDA performance indicw measured were total time (TT), fastest time (FT), mean time (MT) and performance decrement (PD). Both tats involved sprinting or dribbling 7 x 34.2 m with 25 seconds rest intervals (Bangsbo, 1994). Blood sample were collected from fingertip at the end of RSA and RDA tests (zero time recovery), and m 1, 3, 5, 7, 9, and 12 minutes of recovery. Significant differenca were found in peak blood lactate and lactate removal rate for RSA and RDA (p < .05). Low negative correlations were found among total time, mean time and V02m in RSA. While, moderate negative correlations were found among total time, fastast time and V01,“ in RDA. Significant positive correlations were found between performance indices (total time, fastest time, mean time) and lamate removal rate in RSA. As conclusion, the study suggests that V01.“ is correlated with selected RSA and RDA performance indices.